2019
DOI: 10.3892/ol.2019.10388
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic evaluation of resectable colorectal cancer using platelet‑associated indicators

Abstract: Colorectal cancer (CRC) represents the third most common malignancy worldwide. The aim of the present study was to investigate the predictive values of platelet-associated indicators, including platelet count (PLT), plateletcrit (PCT), mean platelet volume (MPV) and platelet distribution width (PDW) in patients with resectable CRC. The current retrospective study included 153 patients who were pathologically diagnosed with resectable CRC. The patients were divided into two groups according to the median value … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…CRC studies with PLT, PDW, MPV and other platelet-related indicators as the study objects had emerged one after another in recent years [10,55] . Platelets not only produce the blood clotting cascade, but also regulate inflammatory response and cancer pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRC studies with PLT, PDW, MPV and other platelet-related indicators as the study objects had emerged one after another in recent years [10,55] . Platelets not only produce the blood clotting cascade, but also regulate inflammatory response and cancer pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Blood routine test (BRT), as one of the most basic peripheral blood biochemical tests, can quickly and accurately detect the values of blood components such as white blood cells (WBC), lymphocytes (LY), red blood cells (RBC), hemoglobin (HGB) and platelets (PLT), as well as other related indicators, in order to effectively indicate abnormalities of infection, anemia and cruor [7][8][9] . In recent years, a wide variety of blood indicators with different changes were concerned and discussed in the study of malignant tumor diseases including CRC: Qian W, et al reported that the post-/pre-treatment MPV (Mean Platelet Volume) ratio were prognostic factors for OS in resectable CRCs [10] ; Preoperative neutrophil-lymphocyte ratio (NLR) and red blood cell distribution width (RDW), especially the independent prediction of NLR, were confirmed as effective biomarkers for clinical diagnosis and prognosis evaluation of esophageal cancers [11] ; In patients with pathologic stage I non-small cell lung cancer undergoing surgical resection, high LY and PLT count from peripheral blood could provide poor prognostic value independently [12] ; Even the ratios between indicators were developed into new indexes, which had fairly good prognostic significance, including NLR, Platelet-to-Lymphocyte Ratio (PLR), Lymphocyte-to-Monocyte ratio (LMR). [13][14][15][16] .…”
Section: Ivyspringmentioning
confidence: 99%
“…Thrombocytosis was reported to have a prognostic role both prior to and after primary tumor removal [16][17][18][19]. Furthermore, studies on CRC and other platelet-related indicators and ratios like mean platelet volume (MPV), the mean platelet volume-platelet count ratio (MPV/PC) and the platelet -lymphocyte ratio (PLR) were conducted recently [19,46,47]. Compared to the healthy controls, CRC patients had significantly lower MPV/PC and significantly higher PLR values [46].…”
Section: Discussionmentioning
confidence: 99%
“…Platelets-associated indicators and platelet counts have been shown associated with the prognosis of resectable lung and colorectal cancers [37][38][39]. In addition to the predictive role of platelets-associated indicators in cancer, platelet counts, or protein markers, Best et.…”
Section: Discussionmentioning
confidence: 99%